Relações de colonialidade e (i)mobilidade em Claire of the sea light, de Edwidge Danticat - Oliveira, Ana Flávia de Morais Faria (2021)
This work aims to analyze the novel Claire of the sea light (2013), by the writer with dual nationality – Haitian and American - Edwidge Danticat. The work is set between the deteriorated spaces of Ville Rose and the favela of Citè Pendue, fictional places in Haiti, where the author discusses the remnants of a violent colonial past, as well as the impacts of migratory movements in the country. The narrative is initially centered on the story of Claire Limyè Lanme Faustin, a poor girl who runs away when she finds out that she would be handed over to Madame Gaëlle's care, however, after this escape, the stories of other characters are presented. Through fragmented and interconnected narratives, the novel deals with coloniality relations and the individual and collective silences and censors of a society plagued by violence, corruption, social disparity and gender inequalities. The purpose of this work is to show how the characters in the novel resist imposed oppression, breaking mainly with silences and censors. Under the bias of postcolonial and decolonial theories and the contribution of topoanalysis, we seek to demonstrate the hierarchical structures that pervade Haiti, especially the class and gender hierarchies. Feminist critique and gender studies have helped us identify the objectification of Haitian women in public and private spaces and have enabled us to understand how these women resist. Instead of limiting themselves to a victimizing discourse, the female characters open new enunciative spaces which contest impositions and inequalities, including gender ones, leading us to the conclusion that Danticat bets on women for the reconstruction of the nation of Haiti.